(untitled) (Research, Society and Development, 2021)
Impacted teeth are those that didn’t erupt in the oral cavity and are located totally or partially inside the bone. This anomaly is multifactorial and occurs due to local and systemic factors. Mandibular second premolars are the class of teeth most affected by impactions, excluding the upper canines and third molars, which in most cases are asymptomatic and are diagnosed by imaging exams. The objective of this article is to report the procedure of extraction of a second premolar included in the mandible, which was impacted between teeth 34 and 36. For extraction of the tooth was made a relaxing buccal incision, osteotomy and odontosection with drill in high rotation, removing it in fragments with the aid of levers. The surgical procedure for extraction of the impacted element, in this case, was of significant relevance, considering its risks and benefits in relation to other treatment options. Therefore, the approach strategy used was successful in conducting the clinical case.